Pendampingan Pengembangan Bisnis Pedagang Kaki Lima (PKL) Sekitar Kampus Universitas Muria Kudus - Febra Rubiyanto; Dennyca Hendriyanto Nugroho (Batara Wisnu : Indonesian Journal of Community Services, 2022)
The presence of street vendors (PKL) can sometimes disturb residents and the government, but their presence can also contribute to moving the economy of a region. The lack of resources owned by street vendors can make their business less developed. Mentoring activities for street vendors are expected to be useful for business continuity and gain knowledge in entrepreneurship. Street vendors around the University of Muria Kudus (UMK) consist of sellers of food, drinks or snacks. Assistance in managing management so that partners will be able to make the right decisions, both management and financial decisions. Partners will think about investment and always adapt to develop their business.